The socio-psychological factors affecting the voting behaviour of the postgraduate politics students: a Q-methodology study - Şener, Turan; Balku, Yaşam; Alkan, Yavuz Selim; Doru, Serkan; Okudan Dernek, Kadriye; Zenginoğlu, Samet (Frontiers in Psychology, 2023)
This study aims to answer the question “Are voting behaviours of postgraduate students, a voter group who are politically educated and well-informed about voting behaviours, affected by socio-psychological factors?.” In particular, if so, it also aims to reveal which socio-psychological factors affect their voting behaviours. The Q-methodology is utilised in this study. The main reason for this methodological preference is that the Q-methodology is a good tool for systematically identifying and examining a particular group’s subjective views that are held around the factors shaping and affecting their voting behaviours by providing factor loadings. Factor loadings, or the cluster of participants, allow us better to illustrate each participant’s association with each of the identified socio-psychological or otherwise factors, similar or different orders of ranking by the participants, to detect individual differences, and, therefore, to indicate (1) whether the socio-psychological factors affect the voting behaviours of the participants, and (2) if so, which socio-psychological factor(s) affects most. This also helps us to conclude that the participants who are mostly associated with one or more factors have similar voting behaviours corresponding to or in opposition to the assumptions of the socio-psychological approach. The participants of the research are 57 postgraduate students studying Political Science and Public Administration at Akdeniz University. The results of the research indicate that most of the participants cluster around two separate factors: while the participants gathered under Factor 1 take their political decisions more rationally and are ready to vote for alternative candidates and political parties in different elections, those who load under Factor 2 are affected by some socio-psychological factors: loyalty to her family’s (the family factor) and inner circles’ political preferences (the inner circle factor), and a long-term commitment and an emotional attachment to a political party and/or the candidate (the time factor). The voting behaviours of the participants gathered under no factors are, however, affected by relatively mixed factors. In addition, it is also revealed that the titles that most differentiate the preferences of the participants cluster around both Factors 1 and 2 are family, education, and rationality.